(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: The only institution that provides security and support without expecting anything in return is family. An individual’s psychological adjustment, problem-solving techniques, sense of self, and capacity for goal-setting are all influenced by their family environment. An individual’s psychological well-being is improved by these interaction patterns operating normally. The objectives: The objectives of this study was to study whether gender differences exist in the psychological well-being of physical education students in Manipur and To study the correlation between family environment and psychological well-being of physical education students in Manipur. Methodology: A cross-sectional study with a sample of 145 physical education students, comprising 53 males and 92 females, was conducted. These students were enrolled in MPES courses organised by various Manipur University and DM University during the academic session 2021-22. Their ages ranged from 22 to 24 years, and they were assessed with Ryff’s Psychological Well-Being Scales and the family environment scales (Kumar & Shrivas). Results: Male physical education students scored higher than their female counterparts in self-acceptance and autonomy, and women scored higher than men in personal growth and positive relations with others. Psychological well-being was significantly correlated with cohesion, expressiveness, care, acceptance, independence, achievement orientation, cultural-moral-religious aspects, active recreational orientation, and organisation at P < 0.05 level. Conflict and control were not significantly correlated with psychological well-being. Conclusion: It was concluded that there was a significant positive relationship between various domains of family environment with psychological well-being among physical education students. To prevent a potential decline in the psychological well-being and psychological issues among physical education students, we should take the early initiative to uncover any dysfunction in families.